KORELASI KETERAMPILAN MEMBACA PEMAHAMAN TEKS LAPORAN HASIL OBSERVASI DENGAN KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VII SMPN 2 NAN SABARIS KABUPATEN PADANG PARIAMAN - Susanti, Peni; Asri, Yasnur; Basri, Irfani (Universitas Negeri Padang, 2018)
ABSTRACTÂ This article was written to know the correlation of reading comprehension skills of the text of the observation result with the skill of writing the text of the observation report of the students of grade VII SMPN 2 Nan Sabaris, Padang Pariaman District. This type of research is quantitative. The method used in this research is descriptive method with correlational design. The population is the seventh grade students of SMPN 2 Nan Sabaris, Padang Pariaman District, which is 105 people divided into four classes. The sample of this study is 32 people. The research consists of two variables, namely the independent variable (reading comprehension skills of the text of the observation report of the seventh grade of SMPN 2 Nan Sabaris Padang Pariaman) and the dependent variable (writing skill of the observation report of grade VII SMPN 2 Nan Sabaris Padang Pariaman). The result of the research shows that for the skill of writing the text of the observation result, it is necessary to read comprehension skill of the observation report. From the results of this study can be concluded that there is a significant relationship (meaning) between reading comprehension skills text report the results of observation with the skills of writing text reports of observations of students of class VII SMPN 2 Nan Sabaris Padang Pariaman on n-1 degrees of freedom at a significant level 95 % with thitung larger than ttable that is 5,652> 1,70.Â Kata kunci; membaca pemahaman, menulis teks laporan hasil observasi